A cross-lingual analysis of attitudinal meaning in publicity discourses of Anglo-American and Chinese universities: a psychological insight from the appraisal system - Zheng, Lu (Frontiers in Psychology, 2025)
IntroductionUniversity publicity discourse is pivotal to global communication, embodying institutional values and cultural identities. While linguistic research on its embedded attitudinal meaning abounds, cross-lingual (English-Chinese) comparative exploration—especially systematic analysis of attitudinal resources in such discourses—remains limited, forming the core focus of this study.MethodsDrawing on the Appraisal System (a robust framework in Systemic Functional Linguistics), this research conducted a comparative analysis of English and Chinese university publicity discourse samples. It extracted and categorized attitudinal resources (Affect, Judgment, Appreciation) and compared their distribution and expressive differences via qualitative and quantitative methods.ResultsSignificant cross-lingual disparities emerged: English discourse used richer emotional expressions (Affect/Appreciation) to enhance affinity, while Chinese discourse prioritized objectivity and authority with restrained emotions. No notable differences were found in Judgment resources. English discourse emphasized moral constraints, whereas Chinese discourse focused more on legal constraints.DiscussionThis study uncovers distinct attitudinal meaning patterns across cultural-linguistic contexts, filling cross-lingual research gaps and refining the Appraisal System. Beyond linguistic theory, it offers practical guidance for universities to optimize cross-cultural publicity and boost global communication effectiveness.